Assessment of evolutionary algorithms in predicting non-deposition sediment transport. Issue 5 (3rd July 2016) - Ebtehaj, Isa; Bonakdari, Hossein
Abstract : In this article, the densimetric Froude number of the flow is estimated using the parameters of volumetric sediment concentration (CV ), the relative depth of flow (d/R), dimensionless particle number (Dgr ) and the overall sediment friction factor (λs ). The particle swarm optimization (PSO) and imperialist competitive algorithms (ICA) were used to estimate the densimetric Froude number. To study the effects of sediment transport parameters on the densimetric Froude number, six different models are presented. The PSO algorithm with root mean square error (RMSE) = 0.014 and mean absolute percentage error (MAPE) = 5.1% present the results with a relatively good accuracy. The accuracy of the results presented for the selected model by the ICA algorithm is also in the form of RMSE = 0.007 and MAPE = 5.6%. Although both algorithms return good results in estimating the densimetric Froude number for the selected model, it should be mentioned that for all the six presented models ICA returns better results than PSO.